Factors Affecting the Demand for Credit of the People's Credit Bank (BPR) In the Ex-Resident of Semarang - Budiyono, Bambang; Kardoyo, Kardoyo; Muhsin, Muhsin (Universitas Negeri Semarang, 2021)
In this millennial era, competition in the banking business is very tight. This competition does not only occur between banks, but competition also comes from other financial institutions that have succeeded in developing new financial products. The problem with the phenomenon that occurs in this research is that the demand for credit in Rural Banks (BPR) is growing rapidly in this millennial era, while People's Credit Banks (BPRs) themselves still have many lacks compared to commercial banks. The purpose of this research is that Rural Banks (BPR) can compete with commercial banks in this millennial era in getting customers. This study used a qualitative approach, in form of descriptive statistical data from the research variables. The population in this study amounted to 144 Rural Banks (BPR) in the Ex-Residency of Semarang. The sampling technique was 65 Rural Banks (BPR) in the Ex-Residency of Semarang. The explanation of the data is accompanied by minimum value, maximum value, mean, variance, and standard deviation. The results of this study are there is a significant and negative influence between the Capital Adequacy Ratio (CAR) on credit demand. There is a significant and positive influence between Non Performing Loans (NPL) on credit demand. There is no significant effect between Return on Total Assets (ROA) on credit demand. There is no significant effect between Return on Total Equity (ROE) on credit demand. There is no significant effect between the Loan to Deposit Ratio (LDR) on credit demand. There is a significant and negative influence between Operational Expenses on Operating Income on credit demand.